Impact of colostrum lactose concentration in relation to metabolomic profiles on kid growth performance of Black Bengal goats - Vo, Tien Thi Phuong; Buranakarl, Chollada; Chamsuwan, Sumonwan; Thammacharoen, Sumpun; Nuntapaitoon, Morakot; Settachaimongkon, Sarn (The Thai Journal of Veterinary Medicine, 2025)
Colostrum composition, including lactose concentration in relation to metabolomic profiles on kids’ growth performance of Black Bengal goats, has not yet been elucidated. Macronutrients, including lactose and metabolomic profiles, were determined in 37 colostrum samples using MilkoScan and 1H-nuclear magnetic resonance technique, respectively. Kids’ growth performance, including birth weight, average daily gain at 0–4 weeks (ADG0-4W), 4–8 weeks (ADG4−8W), and wean weight were determined. A total of 51 metabolites were detected in the colostrum. From the general linear model for univariate analysis, kids born from multiple litter sizes showed lower ADG during the first month postpartum (P = 0.004). The ADG0-4W was correlated positively with lactose (r = 0.434, P < 0.001), betaine (r = 0.263, P < 0.05), glycine (r = 0.303, P < 0.05), and trimethylamine N-oxide (r = 0.372, P < 0.01) but negatively with most metabolites. By using a generalized linear mixed model procedure when kid growth performances were regarded as dependent variables, and the damID was considered as a random effect with birth weight, parity number, and litter size as covariates, kids consumed colostrum with high lactose (P < 0.001) but lower protein, fumarate, malonate, glucose, myo-inositol, vitamin B2, and vitamin B7 (P < 0.05) had higher ADG0-4W. Therefore, growth performance 1 month postpartum was enhanced in kids consuming high lactose with low metabolite contents, which reflects not only the lactose is the main source of energy but also its possible role on the osmotic water-pulling effect on colostrum yield.